The Precision Exploration of Image Super-Resolution Applied into Motion Measurement - Wei, Ye; Hou, Wenhui; Feng, Wei; Jin, Yi; Zhu, Chang'an (Journal of physics. Conference series, 2018)
This paper proposes a new evaluation parameter of image super-resolution reconstruction quality, which is used to determine the influence of super-resolution reconstruction on motion measuring precision. Based on this new evaluation parameter, we respectively employ different algorithms of super-resolution reconstruction with different reconstruction scales, then calculate the motion measuring precision using the corresponding super-resolution image, analyze the impact of image super-resolution technology on the precision of image motion measuring. The experimental results show that only part of the super-resolution algorithms can improve the measuring precision slightly, and prove that under the background of image motion measurement, image super-resolution reconstruction method has the potential to apply to the actual measurement.